Structural change, productive development, and capital flows: Does financial "bonanza" cause premature deindustrialization? - Alberto Botta; Giulano Toshiro Yajima; Gabriel Porcile (Levy Economics Institute of Bard College, 2022)
The outbreak of COVID-19 brought back to the forefront the crucial importance of structural change and productive development for economic resilience to economic shocks. Several recent contributions have already stressed the perverse relationship that may exist between productive backwardness and the intensity of the COVID-19 socioeconomic crisis. In this paper, we analyze the factors that may have hindered productive development for over four decades before the pandemic. We investigate the role of (non-FDI) net capital inflows as a potential source of premature deindustrialization. We consider a sample of 36 developed and developing countries from 1980 to 2017, with major emphasis on the case of emerging and developing economies (EDE) in the context of increasing financial integration. We show that periods of abundant capital inflows may have caused the significant contraction of manufacturing share to employment and GDP, as well as the decrease of the economic complexity index. We also show that phenomena of "perverse" structural change are significantly more relevant in EDE countries than advanced ones. Based on such evidence, we conclude with some policy suggestions highlighting capital controls and external macroprudential measures taming international capital mobility as useful tools for promoting long-run productive development on top of strengthening (short-term) financial and macroeconomic stability.
Keywords: O14; O30; F32; F38; 330; COVID-19; Structural Change; Capital Inflows; Macroprudential Policies